The Kalton-Peck space as a spreading model - Suárez, Jesús (Mathematica Scandinavica, 2024)
The so-called Kalton-Peck space $Z_2$ is a twisted Hilbert space induced, using complex interpolation, by $c_0$ or $\ell _p$ for any $1≤ p eq 2